Contentment-analysis of work environment in ways of safety at agricultural companies leaders and workers in Hajdú-Bihar county - Terjék, László (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
In this paper the author has collected together his examinations about work place envi-ronmental and psychosocial contentment in the circle of farm-leaders and labourers. The direct aim of his examinations was to survey the occupational safety and health (OSH) related contentment in the circle of agricultural enterprises of Hajdú-Bihar County. The used data collection methods were questionnaires and guided interviews. In the question-naire there is a seven-grade Likert-type scale (Malhotra 2005), to evaluate the questioned factors. The result of the examinations shows the similarity and the differences among the two groups regarding to their OSH complacency.